Proceedings ILASS–Europe 2017. 28th Conference on Liquid Atomization and Spray Systems 2017
DOI: 10.4995/ilass2017.2017.4742
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of diesel injector dribble using 3D reconstruction from x-ray and DBI imaging

Abstract: Post-injection dribble is known to lead to incomplete atomisation and combustion due to the release of slow moving, and often surface-bound, liquid fuel after the end of the injection event. This can have a negative effect on engine emissions, performance, and injector durability. To better quantify this phenomenon we present a new image processing approach to quantify the volume and surface area of ligaments produced during the end of injection, for an ECN 'Spray B' 3-hole injector. Circular approximation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The two cameras were both set at 2000 frames per second and 1280 x 800 pixel resolution to capture the detailed air column break-up processes. The generated pairs of images were then digitally cropped and enhanced before being used to reconstruct the three-dimensional structures of the air column using an algorithm developed by Sechenyh et al (2017), as shown in Fig. 3.…”
Section: Formulation Of the Kelvin-helmholtz (Kh) Instabilitymentioning
confidence: 99%
“…The two cameras were both set at 2000 frames per second and 1280 x 800 pixel resolution to capture the detailed air column break-up processes. The generated pairs of images were then digitally cropped and enhanced before being used to reconstruct the three-dimensional structures of the air column using an algorithm developed by Sechenyh et al (2017), as shown in Fig. 3.…”
Section: Formulation Of the Kelvin-helmholtz (Kh) Instabilitymentioning
confidence: 99%